Research on the Risk Management of Supply Chain Risk, Exchange Rate Risk and Economic Recession Risk in Business Organizations - Huang Leyan (SHS Web of Conferences, 2025)
After COVID-19, the economy has become more fluctuating and is exposed to more kinds of risks, such as supply chain risk, exchange rate risk, and economic downturn risk. To maintain a relatively stable position under all kinds of risks, it’s important for firms to develop efficient and useful risk management strategies. In this paper, according to real cases in past years, three important risks to business organizations are introduced. Through comparisons, some suggestions are made about how to construct efficient risk management methods. It can be concluded that futures and low-level long-term hedging strategies are useful in reducing supply chain risk. Interest rate swap contracts and forward foreign exchange contracts are able to reduce exchange rate risk. But for economic recession risk, typical financial derivatives don’t have much effort, diversification is a more efficient risk management method. This paper analyzes efficient risk management methods for the three risks under current environments, providing suggestions and consultations for firms.